Facebook content marketing for Finnish plant-based protein producers - Ivanova, Ekaterina (2021)
In Finland, the consumption of plant-based protein products has been increasing. Despite a wide choice of imported plant-based protein products in supermarkets, Finns tend to favor local brands. Moreover, Finnish plant-based protein products are experiencing an improved export potential owing to outstanding technologies. Thus, plant-based protein products were considered a noteworthy trend in consumer behavior in Finland which deserved studying from the digital marketing perspective.